2020
DOI: 10.3389/fgene.2020.533373
|View full text |Cite
|
Sign up to set email alerts
|

Familial Focal Segmental Glomerulosclerosis With Late-Onset Presentation and R229Q/R291W Podocin Mutations

Abstract: Introduction: Pathogenic variants in different genes have been described as involved in the development of familial focal segmental glomerulosclerosis (FSGS). A more precise genotype-phenotype correlation would be helpful to better characterize the clinical and laboratorial manifestations of this disease, as well as response to treatment. We analyzed podocin (NPHS2) gene variants in 50 members of four generations of a family with late-onset presentation of glomerular disease. Results and Discussion: The NPHS2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…and 310 has been reported in three children who developed ESKD [49]. More recently, Righetti, et al [50]. concluded that compound heterozygous R229Q or R291W variants might be associated with the FSGS phenotype, but neither heterozygous variant was associated with significant proteinuria.…”
Section: Discussionmentioning
confidence: 94%
“…and 310 has been reported in three children who developed ESKD [49]. More recently, Righetti, et al [50]. concluded that compound heterozygous R229Q or R291W variants might be associated with the FSGS phenotype, but neither heterozygous variant was associated with significant proteinuria.…”
Section: Discussionmentioning
confidence: 94%
“…Nephrin directly interacts with podocin (encoded by NPHS2 ) to transport nephrin to the plasma membrane [ 37 ]. NPHS2 mutations lead to the misfolding and mislocalization of podocin and interrupt the proper trafficking of nephrin, causing FSGS [ 38 ]. In addition, nephrin interacts with CD2AP with a subunit of PI3K and subsequently activates the Akt kinase pathway, which is necessary for regulating the actin cytoskeleton [ 39 ].…”
Section: Cytoskeleton Rearrangement In Podocytopathies and Podocyte-c...mentioning
confidence: 99%
“…The mutation of NPHS2 has been reported to occur in 13% of patients that manifested with SRNS before 25 years of age and accounted for the 34% of all 27 common genes in podocytes causing SRNS (10). To date, many novel NPHS2 gene mutations have been discovered and more genotype-phenotype correlations have been published, such as deletion c.988_989delCT, c.725C>T, c622G>A and c.928G>A et al (11)(12)(13). With the advent of the latest next gene screening technology and the development of molecular genome database platforms, more and more pathogenic genetic mutations contributing to pediatric SRNS have been identified in recent years (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%